Pengembangan E-LKPD Berbasis Saintifik Materi Sistem Pernapasan pada Manusia Kelas XI SMA: (Development of E-LKPD Based on Scientific in Human Respiratory System for Senior High School Students Grade XI) - Winda Amthari; Damris Muhammad; Evita Anggereini (BIODIK, 2021)
Student worksheet (LKPD) is a teaching material which can be developed by a teacher to be used in learning process. Based on the observation result in SMAN 2 Kota Jambi, most of the students are still struggling in understanding the human respiratory system material. Electronic LKPD or e-LKPD contains learning material with images and videos which make students learn easier. Teaching material such as e-LKPD can be integrated with scientific approach which stimulates students’ involvement in learning process. This research aims to develop scientific based e-LKPD for human respiratory system material for Senior High School grade XI, to find out about the properness, teachers’ and students’ response, and the effectiveness of e-LKPD in improving learning outcomes.  The development of e-LKPD used ADDIE model which consists of analysis, design, development, implementation, and evaluation. The e-LKPD product has been validated by the media and material experts with very good result. The result of biology teacher’s response and the result of students’ trial on small and big group showed very good result. The result of effectiveness test using paired sample t test showed that there is an effect of using scientific based e-LKPD on human respiratory system material in improving student learning’s outcomes. Thus, scientific based e-LKPD for human respiratory system material is an appropriate teaching material and can improve students’ learning outcomes. Abstrak. Lembar Kerja Peserta Didik (LKPD) merupakan bahan ajar yang dapat dikembangkan oleh guru untuk digunakan dalam pembelajaran. Berdasarkan observasi di SMAN 2 Kota Jambi, sebagian peserta didik mengalami kesulitan dalam  memahami materi sistem pernapasan manusia. LKPD elektronik atau e-LKPD memuat materi pembelajaran yang dilengkapi dengan gambar serta video  yang memudahkan dalam memahami materi tersebut. Bahan ajar seperti e-LKPD dapat diintegrasikan dengan pendekatan saintifik yang merangsang keterlibatan peserta didik dalam proses pembelajaran. Penelitian ini bertujuan untuk mengembangkan e-LKPD berbasis saintifik materi sistem pernapasan pada manusia kelas XI SMA, mengetahui kelayakan, mengetahui respon guru dan peserta didik serta mengetahui efektivitas e-LKPD yang dikembangkan dalam meningkatkan hasil belajar. Pengembangan e-LKPD menggunakan model ADDIE yang terdiri dari tahap analysis, design, development, implementation dan evaluation. Produk e-LKPD divalidasi oleh ahli media dan ahli materi dengan perolehan hasil sangat baik. Hasil respon guru biologi serta ujicoba kelompok kecil dan kelompok besar diperoleh hasil sangat baik. Hasil uji efektivitas menggunakan uji paired sample t test menunjukkan terdapat pengaruh penggunaan e-LKPD berbasis saintifik materi sistem pernapasan pada manusia dalam meningkatkan hasil belajar. Dengan demikian e-LKPD berbasis saintifik materi sistem pernapasan pada manusia yang dikembangkan layak digunakan sebagai bahan ajar dan dapat meningkatkan hasil belajar peserta didik.